Explaining Immigrants' Worries About Ethnic Harassment: Germany, 1986–2004 - Spörlein, Christoph; Schlueter, Elmar (Frontiers in Sociology, 2020)
What factors shape immigrants’ worries about becoming targets of ethnic harassment? This is an important question to ask, but most previous studies restricted their focus to the microlevel only. By contrast, few if any studies examined the possible macrolevel antecedents driving harassment-related worries among immigrants. This study aims to help fill this gap. Focusing on a 20-year period from 1986 to 2004 in Germany, we apply multilevel regression modeling techniques to repeated cross-sectional survey data collected among immigrants of Greek, Italian, Spanish, Turkish, and (ex-)Yugoslavian origin, linked with contextual characteristics. Our central finding is that German citizens’ anti-immigrant prejudice is the key driver of longitudinal differences in immigrants’ harassment-related worries. This association holds net of rival variables, such as fluctuations in media attention to ethnic harassment, as well as across all immigrant groups under study. These results bring us one important step further toward a better understanding of interethnic relations between immigrants and host society members.